Representing Contemporary Immigrant and BIPOC Experiences through USM’s Special Collections - Faherty, Anna; Newell, Zachary; Roy, Jill (Maine Policy Review, 2024)
University of Southern Maine libraries contain two special collections that document communities that are traditionally underrepresented in historical narratives. The Jean Byers Sampson Center for Diversity in Maine documents the history of activism and diversity in Maine, focusing on African American, Jewish, and LGBTQ+ communities. The Franco-American Collection collects materials related to the culture and heritage of Maine’s Franco-American population, those descended from French-Canadian immigrants. While both collections document immigrant experiences in Maine’s history, they do not adequately represent contemporary Maine experiences. This article explores the work of understanding who we represent, who has access, and how we should respond to a developing landscape of interests and needs, and provide a roadmap for cultural heritage institutions to reach these goals as well.